El cuidado que trasciende la presencia. Juego de voces en tensión desde la experiencia de ser madre sustituta (2019)
This article is based on research on the relational experiences of a surrogate mother in relation to herself, with the girls in her charge and with the State. The methodology is the biographical approach, where the narration of the life stories of the surrogate mother is recognized as fundamental to make sense of the relational offerings that she offers to the girls, who were under her care in the after the investigation was carried out. In the results, there is evidence of the tension between the guidelines offered by the State to mediate the relationship between the surrogate mother and the girls in a situation of protection, and the offers that emerge in the link, as well as protective factors that are necessary for the resilient process of girls, as well as attachment, which is specific to the nature of the bond and, the maternal functions that are deployed in that link.